A magnetic hydrogel material capable of repeatedly developing color and a preparation method thereof

By using hydrogel-rich network and core-shell structure magnetic nanoparticles in magnetic hydrogels and using external magnetic fields to regulate the photonic crystal structure, the problem of magnetic photonic crystal losing its color distortion ability in the existing technology is solved, and magnetic hydrocondensation is achieved The instantaneous and repeatable color rendering of glue has a wide range of application prospects.

CN115260528BInactive Publication Date: 2025-01-03DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210836889.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the existing magnetic photonic crystal aqueous phase system is converted to a solid phase, it loses its magnetic responsive color discoloration ability and cannot achieve instantaneous and repeatable color regulation, which limits its use in practical applications.

Method used

The hydrogel network and uniformly dispersed core-shell structure magnetic nanoparticles are used to form and destroy the photonic crystal structure through external magnetic field regulation to achieve instantaneous and repeatable color rendering of magnetic hydrogel materials. The material consists of a hydrogel network composed of agarose and locust bean gum and magnetic nanoparticles such as Fe3O4@SiO2. The magnetic metal oxide core particle size of the magnetic nanoparticles is 80-200nm, and the inorganic metal oxide shell thickness is 20 ~40 nm, prepared by an autoclave and ultrasonic dispersion technology.

Benefits of technology

It realizes the ability to respond instantly and repeatedly regulate color under external magnetic fields, has a stable material structure and has a wide range of application prospects such as display, sensing and anti-counterfeiting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003748838860000011
    Figure HDA0003748838860000011
  • Figure HDA0003748838860000012
    Figure HDA0003748838860000012
  • Figure HDA0003748838860000021
    Figure HDA0003748838860000021
Patent Text Reader

Abstract

The present invention relates to a magnetic hydrogel material with repeatable color development and a preparation method thereof, and belongs to the field of materials. A magnetic hydrogel material with repeatable color development, the magnetic hydrogel material with repeatable color development is composed of a hydrogel-rich network and magnetic nanoparticles uniformly dispersed in the network pores, wherein the magnetic photonic crystal nanoparticles have a core-shell structure, the particle size range of the magnetic metal oxide core is 80-200nm, and the thickness of the inorganic metal oxide shell is 20-40nm; the magnetic metal oxide is one of Fe3O4, CoFe2O4, NiFe2O4, and MnFe2O4; the inorganic metal oxide is one of SiO2, TiO2, and ZrO2. The material has multiple advantages such as instantaneous response to color development under an external magnetic field, remote control of color change, and system stability, and has broad application prospects in the fields of display, sensing, and anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnetic hydrogel material capable of repeatedly developing color and a preparation method thereof, and in particular to a magnetic hydrogel material capable of instantaneously regulating color development under the condition of applying an external magnetic field and a preparation method thereof, and belongs to the field of materials. Background Art

[0002] Magnetic field-induced photonic crystals produce structural colors. They have been widely studied in recent years because of their excellent properties such as rapid response under the condition of applying an external magnetic field and controllable color rendering. 3 O 4 Nanoparticles, as an important magnetically responsive color-changing material, can assemble into a one-dimensional chain-like photonic crystal structure in a magnetic field environment, thus diffracting bright structural colors. However, the flow amorphousness and instability of magnetic nanoparticles dispersed in water largely limit their application in practical scenarios.

[0003] At present, most methods for converting magnetic photonic crystal aqueous phase systems into solid phase systems use polymers or hydrogels to lock the chain structure formed by self-assembly, but the resulting material has a fixed structural color and no longer has the ability to change color in response to magnetism, or combines thermosensitive phase change materials to prepare temperature-responsive hydrogels. When the temperature changes, the volume of the hydrogel changes accordingly, causing the spacing between the nanophotonic crystal units inside the hydrogel to change, thereby producing structural color changes. However, the hydrogel cannot control the instantaneous response of the color and is difficult to display repeatedly. Therefore, exploring a solid material that can display colors repeatedly and has the ability to change color in response to instantaneous response is of great significance and has broad application prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetic hydrogel material and a preparation method thereof which can instantaneously and repeatedly display color under the condition of applying an external magnetic field, which integrates the advantages of instantaneous assembly coloration of liquid magnetic responsive photonic crystal materials and stable structure of solid hydrogels, and has broad application prospects.

[0005] A magnetic hydrogel material capable of repeatedly developing color, the magnetic hydrogel material capable of repeatedly developing color consisting of a hydrogel-rich network and magnetic nanoparticles uniformly dispersed in the pores of the network.

[0006] The magnetic photonic crystal nanoparticles have a core-shell structure, the particle size of the magnetic metal oxide core is in the range of 80 to 200 nm, and the thickness of the inorganic metal oxide shell is in the range of 20 to 40 nm; the magnetic metal oxide is Fe 3 O 4 、CoFe 2 O 4 、NiFe 2 O4 、MnFe 2 O 4 One of the inorganic metal oxides SiO 2 、TiO 2 、ZrO 2 Preferably, the magnetic nanoparticles are Fe 3 O 4 @SiO 2 , Fe 3 O 4 @TiO 2 , Fe 3 O 4 @ZrO 2 、CoFe 2 O 4 @TiO 2 、CoFe 2 O 4 @SiO 2 、CoFe 2 O 4 @ZrO 2 、NiFe 2 O 4 @TiO 2 、NiFe 2 O 4 @ZrO 2 、NiFe 2 O 4 @SiO 2 、MnFe 2 O 4 @ZrO 2 、MnFe 2 O 4 @SiO 2 、MnFe 2 O 4 @TiO 2 At least one of .

[0007] The magnetic hydrogel material capable of repeatedly developing color described in the present invention is a hydrogel material capable of instantaneously and repeatedly regulating color development under the condition of applying an external magnetic field.

[0008] The above-mentioned "color regulation" means that when a magnetic field is applied, the magnetic hydrogel will change color, and the removal of the magnetic field will return to the original color of the magnetic hydrogel. At the same time, the above process can be repeated indefinitely. Therefore, the magnetic hydrogel has the characteristics of instantaneous and repeatable.

[0009] In the magnetic hydrogel material capable of repeatedly developing color according to the present invention, the hydrogel-rich network is a hydrogel with a macroporous mesh structure containing water inside.

[0010] In the magnetic hydrogel material capable of repeatedly developing color according to the present invention, the mass ratio of the hydrogel-rich network to the total amount of magnetic nanoparticles is 1:0.001-0.0158.

[0011] Preferably, the hydrogel-rich network is composed of a hydrogel matrix material, a hydrogel thickener and water, wherein the mass ratio of the hydrogel matrix material to the hydrogel thickener is 1:0.1-1, and the ratio of the total weight of the hydrogel matrix material and the hydrogel thickener to water is 0.1-2 g:10 mL.

[0012] Further preferably, the mass ratio of the hydrogel matrix material to the hydrogel thickener is 7:3.

[0013] Among them, the hydrogel matrix material is polyisopropylacrylamide, polyacrylic acid, polyhydroxyethyl methacrylate, polymethyl methacrylate, polyacrylamide, polyvinyl pyrrolidone, polyvinyl alcohol, hemicellulose, gelatin, and agar; the hydrogel thickener is at least one of locust bean gum, carbomer, Seppic, ammonium acrylamide dimethyltaurate / VP copolymer, xanthan gum, and hydroxyethyl cellulose.

[0014] Furthermore, the hydrogel material is agarose. Agarose is a polysaccharide composed of D-galactose and 3,6 dehydrated L-galactose. In a hot water solution, agarose is a viscous liquid phase. When cooled, the hydrogen bond attraction between the sugar groups causes the polysaccharide chains to spiral and aggregate to form a network structure hydrogel containing a large amount of water inside.

[0015] Furthermore, the thickener is locust bean gum, and the good hydrogel synergistic effect between locust bean gum and agarose is utilized to improve the rupture strength of agarose hydrogel.

[0016] Furthermore, when the compounding ratio of agarose and locust bean gum is 7:3, it has good strength and toughness.

[0017] Preferably, the ratio of the total mass of the added agarose and locust bean gum to water is 0.1-2 g:10 mL.

[0018] Furthermore, the compound glue solution is dissolved at a water bath temperature of 85 to 95°C.

[0019] Furthermore, the water-rich gel material is prepared from agarose, locust bean gum and water, and the mass ratio of agarose to locust bean gum is 7:3.

[0020] Preferably, the magnetic nanoparticles are prepared as follows: a mixed solvent of a metal salt, diethylene glycol and ethylene glycol is added to a high-pressure reactor, and then a sodium citrate ligand and a base are added to prepare magnetic metal oxide core nanoparticles in a high-pressure reactor; an aqueous dispersion of the magnetic metal oxide core nanoparticles, ammonia water and anhydrous ethanol are mixed and ultrasonically dispersed, an inorganic metal oxide precursor is added at room temperature, and the reaction is stirred at a high speed, thereby coating the surface of the magnetic metal oxide core nanoparticles with a stable inorganic oxide shell layer to obtain coated magnetic nanoparticles.

[0021] The metal salt is FeCl 3 、CoCl 2 ,Ni(NO 3 ) 2 、MnCl 2 ; The magnetic nanocluster core material is Fe 3 O 4 、CoFe 2 O 4 、NiFe 2 O 4 、MnFe 2 O 4 ; The inorganic oxide precursor is tetraethyl orthosilicate, tetrabutyl titanate and tetrabutyl zirconate, wherein the diameter of the magnetic metal oxide core nanoparticles is controlled by the amount of added alkali, and the concentration of the magnetic metal oxide core nanoparticles aqueous dispersion is 15-16 mg / mL; the inorganic oxide precursor and the magnetic metal oxide core nanoparticles aqueous dispersion are added in a volume ratio of 0.03-0.06:1.

[0022] In the above technical solution, the particle size of the magnetic metal oxide core of the magnetic nanoparticles can be controlled within the range of 80 to 200 nm by adding diethylene glycol and ethylene glycol reagents in a volume ratio of 3:1 to 1:3 respectively.

[0023] Another object of the present invention is to provide a method for preparing the above-mentioned magnetic hydrogel material capable of repeatedly developing color.

[0024] A method for preparing a magnetic hydrogel material capable of repeatedly developing color, the method comprising the following steps:

[0025] (1) preparing a magnetic photonic crystal nanoparticle aqueous dispersion, wherein the concentration of the photonic crystal nanoparticle dispersion is 10 to 20 mg / mL;

[0026] (2) adding the hydrogel material and its thickener into deionized water according to the mass ratio, dissolving them in a water bath at 85-95° C. under magnetic stirring to obtain a composite gel solution;

[0027] (3) The composite glue obtained in step (2) and the aqueous dispersion of magnetic photonic crystal nanoparticles obtained in step (1) are mixed in a volume ratio of 1:1, cooled to 45-60° C., stirred at 400-600 rpm to remove bubbles and mix them evenly, loaded into a mold, and allowed to stand and solidify under an external magnetic field at room temperature to obtain a magnetic hydrogel material with repeatable color development.

[0028] The beneficial effects of the present invention are as follows: a hydrogel material that can produce color repeatedly under the control of an external magnetic field is invented. First, the hydrogel matrix material and its thickener are dissolved in boiling water by the "one-pot method" to form a suspended colloid, which is then mixed with self-prepared magnetic colloidal particles, cooled to 45-60°C and stirred at high speed for several minutes, and then the mixed colloid is poured into a mold, left to stand under an external magnetic field, and cooled at room temperature to form a hydrogel. During the gradual cooling process, the suspended colloid gradually coils into a rope shape by relying on the intermolecular hydrogen bond attraction. The rope-like micelles are intertwined and coiled to form a large mesh hydrogel framework. The magnetic particles dispersed therein still maintain a certain fluidity and can self-assemble into photonic crystals under an external magnetic field to produce structural colors. The material has many advantages such as instantaneous response to color production under an external magnetic field, remote control of color changes, and stable system. It has broad application prospects in the fields of display, sensing, anti-counterfeiting, etc.

[0029] The hydrogel material of the present invention is preferably agarose, which is a natural linear polymer that can be dissolved in boiling water. After cooling, it can form a network structure by relying on the attraction of hydrogen bonds. After compounding with thickeners such as locust bean gum, the viscosity and strength of the resulting hydrogel are improved. The agarose hydrogel network has a large water content and does not contain charged groups, which will not destroy the dispersion stability of magnetic particles. It is an ideal colloidal photonic crystal matrix material. By dispersing the self-prepared magnetic response color-changing photonic crystal material into the hydrogel network, a membrane material that can remotely control the color by applying an external magnetic field is prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 (a) (b) are respectively the Fe 3 O 4 and Fe 3 O 4 @SiO 2 Scanning electron microscope (SEM) images of magnetic nanoparticles, (c) and (d) are respectively the Fe 3 O 4 and Fe 3 O 4 @SiO 2 Transmission electron microscopy (TEM) image of magnetic nanoparticles.

[0031] Figure 2 The Fe 3 O4 Magnetic nanoparticles and Fe 3 O 4 @SiO 2 Magnetic hysteresis loop of magnetic nanoparticles at 300K.

[0032] Figure 3 The Fe 3 O 4 Magnetic nanoparticles and Fe 3 O 4 @SiO 2 XRD diffraction pattern of magnetic nanoparticles.

[0033] Figure 4 The Fe 3 O 4 Magnetic nanoparticles and Fe 3 O 4 @SiO 2 ZFC-FC curves of magnetic nanoparticles at 500 Oe.

[0034] Figure 5 The Fe 3 O 4 @SiO 2 Reflection spectra of photonic crystals formed by colloidal solutions under different magnetic fields.

[0035] Figure 6 1 and 2 are the reflection spectra of the magnetic hydrogel materials obtained in Examples 1, 2, 4 and 5 under a magnetic field, which are respectively agarose & xanthan gum magnetic hydrogel, agarose & carbomer magnetic hydrogel, agarose & locust bean gum magnetic hydrogel and agarose & hydroxyethyl cellulose magnetic hydrogel.

[0036] Figure 7 The Fe 3 O 4 @SiO 2 Digital photo of colloidal solution forming photonic crystal under external magnetic field, with magnetic field strength of 212Gs to 1218Gs.

[0037] Figure 8 (a) is a photograph of the photonic crystal film material of the present invention before a magnetic field is applied, Figure 8 (b), (c), and (d) are digital photos of the photonic crystal film material changing color in response to a magnetic field. DETAILED DESCRIPTION

[0038] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0039] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described, agarose is of electrophoresis grade, and other reagents are commercially available unless otherwise specified.

[0040] One of the specific implementations:

[0041] A method for preparing a magnetic hydrogel material capable of repeatedly developing color, the method comprising the following steps:

[0042] (1) Using the solvothermal method, ferric chloride was used as the iron source, sodium citrate was added, and diethylene glycol and ethylene glycol with a volume ratio of 3:1 to 1:3 were used as mixed solvents. After heating, anhydrous sodium acetate was added. After continuing the reaction, the reaction solution was placed in a reactor and heated at a constant temperature for 10 hours to obtain superparamagnetic Fe 3 O 4 Nanoparticles, magnetic nanoparticles, and then add oxide precursors and stir to react, thereby coating the inorganic nanomaterials on the Fe 3 O 4 surface, enhance its dispersion stability, and disperse the product in deionized water to obtain a monodispersed Fe 3 O 4 @SiO 2 Nanoparticle aqueous dispersion, Fe 3 O 4 @SiO 2 The solid-liquid ratio of the aqueous dispersion is 0.1:100 to 2:100.

[0043] The sodium citrate acts as a ligand to enhance the Fe 3 O 4 The nanoparticles are monodisperse to avoid agglomeration; the superparamagnetic Fe 3 O 4 The diameter of the nanoparticles is controlled by the amount of anhydrous sodium acetate added; the oxide precursors are tetraethyl orthosilicate, tetrabutyl titanate and tetrabutyl zirconate, and the precursors are combined with superparamagnetic Fe 3 O 4 The nanoparticle aqueous dispersion is added in a volume ratio of 0.03 to 0.06:1.

[0044] (2) Using the "one-pot method", agarose and thickener were added to the reaction vessel at a mass ratio of 1:0.1-1, and then 10 mL of water (the ratio of the total mass of agarose and thickener added to water was 0.1-2 g:10 mL) was added and placed in a 90°C water bath with magnetic stirring to dissolve. Take 5 mL of the gel dissolved in boiling water and 5 mL of the prepared Fe 3 O 4 @SiO 2 The dispersion was mixed, cooled to 60°C for degassing, stirred at high speed for 3 minutes, and then the reaction gel was placed at room temperature to cool the hydrogel.

[0045] The thickener is one of locust bean gum, carbomer (Carbopol 1981), Sepinov EMT-10, acrylamide dimethyl taurate ammonium / VP copolymer (Aristoflex AVC), xanthan gum (Keltrol), and hydroxyethyl cellulose (Ashland).

[0046] (3) The composite glue obtained in step (2) and the Fe 3 O 4 @SiO 2 The dispersions were mixed at a volume ratio of 1:1, cooled to 60°C, stirred at 400-600 rpm to remove bubbles and mix evenly, loaded into a mold, and allowed to stand and solidify under a magnetic field at room temperature to obtain a magnetic hydrogel material with repeatable color development.

[0047] Example 1

[0048] 1. Add 60 mL of diethylene glycol (DEG) and 20 mL of ethylene glycol (EG) to a beaker to obtain a mixed solution. Weigh 1.62 g of anhydrous ferric chloride (FeCl 3 ) into a 250mL three-necked flask, and quickly add the prepared mixed solution into the three-necked flask to avoid FeCl 3 Deliquesce, then add 1g sodium citrate dihydrate (Na 3 Cit·2H 2 O), heated to 120°C for 30 min under mechanical stirring at 400 rpm. Add 5.2 g of anhydrous sodium acetate (NaAc) to the reaction solution, continue the reaction for 1 h, then add the reaction solution to a 100 mL reactor and place it in an oven at 200°C for 10 h. After natural cooling, pour off the supernatant, transfer the black product at the bottom to a beaker with a mixture of anhydrous ethanol and deionized water (V:V = 1:1), and stand in a magnetic field after ultrasonication to adsorb the magnetic product Fe 3 O 4 Nanoparticles, if the magnetic product is not completely adsorbed to the bottom of the beaker by the magnet after more than 30 minutes, add a small amount of dilute sodium chloride solution. After repeated magnetic separation, the product is dispersed in 10mL deionized water to obtain Fe 3 O 4 Nanoparticle dispersion. Ultrasonicate the dispersion to make it uniform, take 200 μL of the dispersion and drop it into a container with a mass of 0.1456 g, put it into a 70°C oven to dry, then take it out and weigh the dry Fe 3 O 4 The total mass of the powder container is 0.157g, then Fe 3 O 4 The mass of the powder is 0.0114 g, and the concentration of the dispersion is 0.057 g / mL.

[0049] 2. Add 1.75 mL of the above Fe 3 O 4 The nanoparticle dispersion was diluted to 20 mL with water, 3 mL of 25% pure ammonia water was added, ultrasonicated for 10 min, 100 mL of anhydrous ethanol was added and ultrasonicated for 10 min, 325 μL of tetraethyl orthosilicate (TEOS) was quickly injected under mechanical stirring at 530 rpm, and the reaction was stopped after stirring in a water bath at 24 ° C for 1 h. The reaction solution was poured into a beaker and magnetically separated, and washed with anhydrous ethanol and deionized water respectively, and then the product was dispersed in 10 mL of deionized water to prepare Fe 3 O 4 @SiO 2 The solid content of the magnetic nanoparticle dispersion was determined to be 15.8 mg / mL.

[0050] From Fe 3 O 4 and Fe 3 O 4 @SiO 2 SEM and TEM images of magnetic nanoparticles (attached Figure 1 ) It can be seen that the Fe 3 O 4 The average particle size of the nanoparticles is 160nm. 3 O 4 @SiO 2 The average particle size of the nanoparticles is 190nm. The particles are spherical before and after coating and have good monodispersity. Figure 2 ) and zero cold field-cold field curve (attached Figure 4 ) It can be seen that the hysteresis loops of the products before and after coating pass through the origin, and the ZFC curves before and after coating have the highest points at 148.5K and 190.3K, respectively, indicating that the material has superparamagnetism. From the XRD diagram of the material (Attached Figure 3 ) It can be seen that the diffraction peak position is similar to that of spinel Fe 3 O 4 The characteristic peaks are completely consistent, indicating that the obtained product is Fe 3 O 4 . The reflectance spectrum of the coated magnetic particle aqueous dispersion assembled under a magnetic field (see Appendix Figure 5 ) and digital photos (with Figure 7 ) It can be seen that the magnetic particles assemble into photonic crystals under the magnetic field, and their reflection peak covers almost the entire visible light range. As the magnetic field gradually increases (the distance between the magnet and the sample decreases), the sample changes from red to blue.

[0051] 3. Weigh 0.21g agarose, 0.09g locust bean gum (m:m=7:3), add 10mL deionized water, put into a 90℃ water bath and stir with magnetic stirring to dissolve, and obtain a uniform composite glue solution. Take 5mL of fully dissolved glue solution and mix with 5mL of self-prepared Fe 3 O 4 @SiO 2 The magnetic nanoparticle dispersion was mixed, cooled to 60°C for degassing, stirred at high speed for 3 minutes, poured into a mold, and cooled and solidified at room temperature under an external magnetic field to obtain a magnetic hydrogel material with repeatable color development.

[0052] From the reflectance spectrum of magnetic hydrogel materials (Appendix Figure 6 ) and digital photos of color development in response to magnetic fields (attached Figure 8 ) It can be seen that when no magnetic field is applied, the material appears brown. When a magnetic field is applied, the magnetic nanoparticles inside the hydrogel assemble to form a photonic crystal, which diffracts structural color.

[0053] Example 2

[0054] Carbopol (Carbopol 1981) was used to replace the locust bean gum in Example 1, Fe 3 O 4 @SiO 2 The preparation method of nanoparticles is consistent with that in Example 1. Weigh 1% agarose, 0.5% carbomer, add 10 mL of deionized water, put it in a 90°C water bath and stir to dissolve to obtain a compound glue solution. Take 5 mL of the compound glue solution and the magnetic nanoparticle dispersion solution, mix them, cool to 60°C for degassing, stir at high speed for 3 minutes, pour them into a mold, and cool and solidify at room temperature under the condition of applying an external magnetic field to obtain a magnetic hydrogel material with repeatable color development. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0055] Example 3

[0056] Using acryloyldimethyl ammonium taurine / VP copolymer (Aristoflex AVC) instead of locust bean gum in Example 1, Fe 3 O 4 @SiO 2The preparation method of nanoparticles is consistent with that in Example 1. Weigh 1% agarose, 0.3% ammonium acryloyldimethyl taurate / VP copolymer, add 10 mL of deionized water, put it in a 90°C water bath and stir to dissolve to obtain a compound glue solution. Take 5 mL of the compound glue solution and 5 mL of the magnetic nanoparticle dispersion solution and mix them, cool to 60°C for degassing, stir at high speed for 3 minutes, pour into a mold, cool and solidify at room temperature under the condition of applying an external magnetic field to obtain a magnetic hydrogel material that can repeatedly display color. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0057] Example 4

[0058] Xanthan gum (Keltrol) was used to replace the locust bean gum in Example 1, Fe 3 O 4 @SiO 2 The preparation method of nanoparticles is consistent with that in Example 1. Weigh 1% agarose, 0.5% xanthan gum, add 10 mL of deionized water, put into a 90°C water bath and stir to dissolve to obtain a compound glue solution. Take 5 mL of the compound glue solution and 5 mL of the magnetic nanoparticle dispersion solution and mix them, cool to 60°C for degassing, stir at high speed for 3 minutes, pour into a mold, cool and solidify at room temperature under the condition of applying an external magnetic field, and obtain a magnetic hydrogel material with repeatable color development. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0059] Example 5

[0060] Hydroxyethylcellulose (Ashland) was used to replace the locust bean gum in Example 1. 3 O 4 @SiO 2 The preparation method of nanoparticles is consistent with that in Example 1. Weigh 1% agarose, 0.8% hydroxyethyl cellulose, add 10 mL of deionized water, put into a 90°C water bath and stir to dissolve to obtain a compound glue solution. Take 5 mL of the compound glue solution and 5 mL of the magnetic nanoparticle dispersion solution and mix them, cool to 60°C for degassing, stir at high speed for 3 minutes, pour into a mold, cool and solidify at room temperature under an external magnetic field, and obtain a magnetic hydrogel material with repeatable color development. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0061] Embodiments 6 to 10

[0062] The total mass of agarose and its thickener is changed to 1 g, and the selected thickeners are locust bean gum, carbomer, ammonium acryloyldimethyltaurate / VP copolymer, xanthan gum, and hydroxyethyl cellulose in Examples 1 to 5. Other conditions are kept consistent with Examples 1 to 5. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0063] Examples 11 to 15

[0064] The total mass of agarose and its thickener is changed to 2 g, and the selected thickeners are locust bean gum, carbomer, ammonium acryloyldimethyltaurate / VP copolymer, xanthan gum, and hydroxyethyl cellulose in Examples 1 to 5. Other conditions are kept consistent with Examples 1 to 5. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0065] Example 16

[0066] Polyisopropylacrylamide was used to replace the agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can control the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0067] Embodiment 17

[0068] Polyacrylic acid was used instead of agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can control the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0069] Embodiment 18

[0070] Poly(hydroxyethyl methacrylate) was used to replace the agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can control the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0071] Embodiment 19

[0072] Polymethyl methacrylate was used to replace the agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can control the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0073] Embodiment 20

[0074] Polyacrylamide was used instead of agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can regulate structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0075] Embodiment 21

[0076] Polyvinyl pyrrolidone was used to replace the agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can control the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0077] Embodiment 22

[0078] Polyvinyl alcohol was used instead of agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can regulate structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0079] Embodiment 23

[0080] Hemicellulose was used instead of agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0081] Embodiment 24

[0082] Gelatin was used to replace agarose in Example 1, and other conditions were the same as those in Example 1. The obtained magnetic hydrogel material can regulate structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0083] Embodiment 25

[0084] Use Fe 3 O 4 @TiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0085] Embodiment 26

[0086] Use Fe 3 O 4 @ZrO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0087] Embodiment 27

[0088] Utilizing CoFe 2 O 4 @TiO 2 Instead of Fe in Example 1 3 O 4@SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0089] Embodiment 28

[0090] Utilizing CoFe 2 O 4 @SiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0091] Embodiment 29

[0092] Utilizing CoFe 2 O 4 @ZrO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0093] Embodiment 30

[0094] Utilize NiFe 2 O 4 @TiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0095] Embodiment 31

[0096] Utilize NiFe 2 O 4 @ZrO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0097] Embodiment 32

[0098] Utilize NiFe 2 O 4@SiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0099] Embodiment 33

[0100] Utilize MnFe 2 O 4 @ZrO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0101] Embodiment 34

[0102] Utilize MnFe 2 O 4 @SiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

[0103] Embodiment 35

[0104] Utilize MnFe 2 O 4 @TiO 2 Instead of Fe in Example 1 3 O 4 @SiO 2 , and other conditions are consistent with those in Example 1. The obtained magnetic hydrogel material can regulate the structural color by applying an external magnetic field, and has a rapid response effect to the magnetic field.

Claims

1. A magnetic hydrogel material capable of repeatedly developing color, characterized in that: The reproducible color-developing magnetic hydrogel material is composed of a hydrogel-rich network and magnetic nanoparticles uniformly dispersed in the network pores. The hydrogel network is composed of a hydrogel matrix material, a hydrogel thickener and water; the magnetic nanoparticles have a core-shell structure, the particle size of the magnetic metal oxide core is in the range of 80 to 200 nm, and the thickness of the inorganic metal oxide shell is 20 to 40 nm; the magnetic metal oxide is one of Fe3O4, CoFe2O4, NiFe2O4, and MnFe2O4; the inorganic metal oxide is one of SiO2, TiO2, and ZrO2; the hydrogel matrix material is agarose, and the hydrogel thickener is locust bean gum. The material is prepared according to the following method, which specifically comprises the following steps: (1) preparing a magnetic nanoparticle aqueous dispersion, wherein the concentration of the magnetic nanoparticle aqueous dispersion is 15 to 16 mg / mL; (2) adding the hydrogel matrix material and the hydrogel thickener into deionized water according to the mass ratio, and dissolving them in a water bath at 85 to 95° C. with magnetic stirring to obtain a composite glue solution; (3) The composite glue obtained in step (2) is mixed with the aqueous dispersion of magnetic nanoparticles obtained in step (1) in a volume ratio of 1:1, cooled to 45-60° C., stirred at 400-600 rpm to remove bubbles and mix them evenly, loaded into a mold, and allowed to stand and solidify under an external magnetic field at room temperature to obtain a magnetic hydrogel material with repeatable color development.

2. The material according to claim 1, characterized in that: The magnetic nanoparticles are at least one of Fe3O4@SiO2, Fe3O4@TiO2, Fe3O4@ZrO2, CoFe2O4@TiO2, CoFe2O4@SiO2, CoFe2O4@ZrO2, NiFe2O4@TiO2, NiFe2O4@ZrO2, NiFe2O4@SiO2, MnFe2O4@ZrO2, MnFe2O4@SiO2, and MnFe2O4@TiO2.

3. The material according to claim 1, characterized in that: In the magnetic hydrogel material capable of repeatedly developing color, the mass ratio of the hydrogel-rich network to the total amount of magnetic nanoparticles is 1:0.001-0.0158.

4. The material according to claim 1, characterized in that: The mass ratio of the hydrogel matrix material to the hydrogel thickener is 1:0.1-1, and the ratio of the total weight of the hydrogel matrix material and the hydrogel thickener to water is 0.1-2g:10mL.

5. The material according to claim 4, characterized in that: The mass ratio of agarose to locust bean gum is 7:

3.

6. The material according to claim 1, characterized in that: The magnetic nanoparticles are prepared according to the following method: adding a mixed solvent of a metal salt, diethylene glycol and ethylene glycol into a high-pressure reactor, and then adding a sodium citrate ligand and a base to prepare magnetic metal oxide core nanoparticles in the high-pressure reactor; mixing an aqueous dispersion of the magnetic metal oxide core nanoparticles, ammonia water and anhydrous ethanol, and then ultrasonically dispersing them, adding an inorganic metal oxide precursor at room temperature, and reacting by high-speed stirring, thereby coating the surface of the magnetic metal oxide core nanoparticles with a stable inorganic oxide shell layer to obtain coated magnetic nanoparticles; The metal salts are FeCl3, CoCl2, Ni(NO3)2, and MnCl2; the inorganic oxide precursors are tetraethyl orthosilicate, tetrabutyl titanate, and tetrabutyl zirconate; wherein the diameter of the magnetic metal oxide core nanoparticles is controlled by the amount of added alkali, and the concentration of the magnetic metal oxide core nanoparticles aqueous dispersion is 15 to 16 mg / mL; the inorganic oxide precursors and the magnetic metal oxide core nanoparticles aqueous dispersion are added in a volume ratio of 0.03 to 0.06:

1.

7. The material according to claim 6, characterized in that: The particle size of the magnetic metal oxide core of the magnetic nanoparticles is regulated within the range of 80 to 200 nm by adding diethylene glycol and ethylene glycol reagents in a volume ratio of 3:1 to 1:

3.

8. The method for preparing the magnetic hydrogel material capable of repeatedly developing color according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) preparing a magnetic nanoparticle aqueous dispersion, wherein the concentration of the magnetic nanoparticle aqueous dispersion is 15 to 16 mg / mL; (2) adding the hydrogel matrix material and the hydrogel thickener into deionized water according to the mass ratio, and dissolving them in a water bath at 85 to 95° C. with magnetic stirring to obtain a composite glue solution; (3) The composite glue obtained in step (2) is mixed with the aqueous dispersion of magnetic nanoparticles obtained in step (1) in a volume ratio of 1:1, cooled to 45-60° C., stirred at 400-600 rpm to remove bubbles and mix them evenly, loaded into a mold, and allowed to stand and solidify under an external magnetic field at room temperature to obtain a magnetic hydrogel material with repeatable color development.